Perfect deterrence - Zagare, Frank C.; Kilgour, D. Marc (Cambridge studies in international relations, 2000)
An important and timely contribution to international relations and political science, this is the first general analysis of deterrence since the end of the Cold War. Using non-cooperative game theory, the authors offer a new approach to deterrence - Perfect Deterrence Theory - which they apply unilateral and mutual direct-deterrence relationships, and to extended-deterrence relationships supported by deployment policies such as Massive Retaliation and Flexible Responses. The authors focus on the relationship among capability, preferences, credibility, and outcomes to achieve a new understanding of threats and responses. With the application of deterrence theory on diverse social settings, and historical examples from before, during, and after the Cold War, this book provides a welcome new examination of the subject.